Higher density of CD4+ T cell infiltration predicts severe renal lesions and renal function decline in patients with diabetic nephropathy - Han, Qianqian; Xu, Huan; Li, Lin; Lei, Song; Li, Ziyao; Zhao, Lijun; Liu, Fang (Frontiers in Immunology, 2024)
BackgroundMore evidence have shown that the combination of immune and inflammatory mechanism was critical in diabetic nephropathy (DN). However, the relationship between CD4+ T cells and the development of DN is still unclear. Therefore, this study will focus on this issue from the perspective of clinicopathology.MethodsFrom September 2019 to December 2022, a total of 112 adult patients with DN were enrolled in the study. According to the density of CD4+ T cell infiltration based on immunostaining, the patients were divided into high-CD4 group (56 patients) and low-CD4 group (56 patients). Another 25 diabetic patients with minimal change disease (non-diabetic nephropathy, NDN) was reviewed as control group in clinical and molecular analysis. The clinical parameters, morphological features, and molecular characteristics were compared. The predictive value of CD4+ T cells for DN prognosis was also investigated.ResultsDN patients in the high-CD4 group suffered from higher proteinuria and lower estimated glomerular filtration rate (eGFR) level than those in the low-CD4 group and NDN patients. Renal biopsy in the high-CD4 group presented with more severe glomerular lesions, higher density of interstitial inflammation, and more severe tubular atrophy/interstitial fibrosis than in the low-CD4 group. Multivariate logistic analysis indicated that the density of CD4+ T cell infiltration could independently predict the severity of tubular atrophy/interstitial fibrosis. In addition, more severe mitochondrial damage of renal tubular epithelial cells and a more obvious expression of Bcl6, IL-6, STAT3, and TGFβ1 were observed in DN patients of the high-CD4 group, indicating the possible mechanism of CD4+ T cells involving the progression of DN. Multivariate Cox regression analysis revealed that a higher intensity of interstitial CD4+ T cell deposition remained as an independent predictor of the double endpoint with doubling of baseline serum creatinine or end-stage renal disease.ConclusionThe high density of CD4+ T cell infiltration was associated with renal function decline and severity of renal lesions and predicted poor renal survival for DN patients.